SEMARANG CITY GOVERNMENT ROLE IN CONSERVATION AND ENVIRONMENTAL PROTECTION TO THE CAPITAL OF THE NATIONAL HERITAGE IN INDONESIA - Achmad J Pamungkas; Carlito Da Costa (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Semarang is the capital of Central Java province and categorized in major cities in Indonesia. The government's role in keeping pest preservation and protection of the environment with menegedepankan balance the economic aspects, protection of cultural heritage and the environment. In the application of conservation and environmental protection in Semarang Semarang city government take strategic steps to perform the functionalization of green open land and the old town that could be developed as a tourist attraction that has the principle of conservation of renewable and environmental protection. Monitoring and environment control for business development players so it does not harm the public, including the empowerment of management Waste that not cause pollution. Keywords: City Government, Conservation and Protection, Environment